ANALISIS SIFAT FISIKA DAN MEKANIKA PAPAN LAMINASI KOMBINASI KAYU SENGON BAMBU PETUNG DAN KEMIRI BAMBU PETUNG - Febriana Tri Wulandari; Radjali Amin; Dini Lestari (Universitas Lambung Mangkurat, 2023)
Bamboo has various advantages such as relatively cheap price, fast growing, physical and mechanical properties comparable to wood, and suitable for application with existing processing technologies. A combination of wood and bamboo laminated boards is an attractive choice in wood and bamboo processing. Previous studies have shown that testing of physical and mechanical properties has been carried out on laminated boards made from wood or bamboo only. Information regarding laminated boards with a combination of wood and non-timber is still very limited. Laminate boards are made from a combination of sengon-petung bamboo and kemiri-petung wood. The selection of sengon and candlenut wood as raw materials because they have a light specific gravity of 0.4 and 0.33-0. Wood with a light to medium density is very suitable for use as a raw material for laminated boards due to easier penetration of the adhesive onto the wood surface. The aim of this study was to investigate the effect of a combination of petung bamboo sengon wood and petung bamboo candlenut wood on the physical and mechanical properties of laminated boards. The method used was an experimental method with a non-factorial design with 2 treatments and 3 replications. The combined type treatment had no significant effect on the density, thickness expansion, thickness shrinkage and MoR tests, while the MoE and moisture content tests had a significant effect. Testing the physical and mechanical properties, the laminated board combination of candlenut wood and petung bamboo (J2) has a higher value than the combination of sengon wood and petung bamboo (J1). Based on the test results, the combination of the combination of kemiri wood, bamboo petung and sengon wood, bamboo petung is included in the strength class III which can be used for protected heavy construction purposesBambu memiliki berbagai kelebihan seperti harga yang relative murah, cepat tumbuh, memiliki sifat fisika dan mekanika sebanding dengan kayu, dan cocok diaplikasikan dengan teknologi pengolahan yang telah ada. Papan laminasi kombinasi dari kayu dan bambu menjadi pilihan yang menarik dalam pengolahan kayu dan bambu. Penelitian sebelumnya menunjukkan bahwa pengujian sifat fisika dan mekanika telah dilakukan pada papan laminasi berbahan baku kayu atau atau bambu saja. Informasi mengenai papan laminasi dengan kombinasi kayu dan non kayu masih sangat terbatas. Papan laminasi dibuat dari kombinasi kayu sengon-bambu petung dan kayu kemiri-bambu petung. Pemilihan kayu sengon dan kemiri sebagai bahan baku karena memiliki berat jenis ringan yaitu 0,4 dan 0,33-0. Kayu dengan berat jenis ringan sampai sedang sangat cocok digunakan sebagai bahan baku papan laminasi terkait penetrasi perekat lebih mudah ke permukaan kayu. Penelitian bertujuan untuk pengaruh kombinasi kayu sengon bambu petung dan kayu kemiri bambu petung terhadap sifat fisika dan mekanika papan laminasi. Metode yang digunakan metode eksperimen dengan rancangan non faktorial dengan 2 perlakuan dan 3 kali ulangan. Perlakuan jenis kombinasi berpengaruh tidak nyata pada pengujian kerapatan, pengembangan tebal, penyusutan tebal dan MoR sedangkan pada pengujian MoE dan kadar air berpengaruh nyata. Pengujian sifat fisika dan mekanika maka papan laminasi kombinasi kayu kemiri dan bambu petung (J2) memiliki nilai yang lebih tinggi dibandingkan dengan papan laminasi kombinasi kayu sengon dan bambu petung (J1). Berdasarkan hasil pengujian papan laminasi kombinasi kayu kemiri bambu petung dan kayu sengon bambu petung masuk dalam kelas kuat III yang dapat dimanfaatkan untuk keperluan konstruksi berat yang terlindungi.